2022
DOI: 10.1080/0886022x.2022.2126789
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK-PGC-1α pathway ameliorates peritoneal dialysis related peritoneal fibrosis in mice by enhancing mitochondrial biogenesis

Abstract: Background The pathogenesis of peritoneal dialysis (PD)-related peritoneal fibrosis (PF) is not clearly understood, and current treatment options are limited. Methods In this study, the effect of PD-related PF on mitochondrial biogenesis was investigated, and the effect of activation of the adenosine monophosphate-activated protein kinase (AMPK)-PGC-1α (peroxisome proliferator-activated receptor γ coactivator-1α) pathway on PF was evaluated in mice. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Compared with the D group, the DP group had a lower mtDNA copy number, which was increased by silibinin (Figure 2e). Mitochondrial biogenesis is regulated by the PGC‐1α‐mitochondrial transcription factor A (TFAM)–nuclear respiratory factor‐2 (NRF2)–nuclear respiratory factor‐1 (NRF1) pathway (Wu et al, 2022). We found that PGC‐1α, TFAM and NRF2 were significantly down‐regulated at the transcriptional level in the DP group compared with the D group.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the D group, the DP group had a lower mtDNA copy number, which was increased by silibinin (Figure 2e). Mitochondrial biogenesis is regulated by the PGC‐1α‐mitochondrial transcription factor A (TFAM)–nuclear respiratory factor‐2 (NRF2)–nuclear respiratory factor‐1 (NRF1) pathway (Wu et al, 2022). We found that PGC‐1α, TFAM and NRF2 were significantly down‐regulated at the transcriptional level in the DP group compared with the D group.…”
Section: Resultsmentioning
confidence: 99%
“…In human peritoneal MCs, high glucose PDF induced excessive ROS production and lipid peroxidation with oxidative DNA damage [ 197 ]. In mice, PDF exposure downregulated the adenine monophosphate (AMP) activated protein kinase (AMPK)- peroxisome proliferator activated receptor-gamma coactivator-1 alpha (PGC-1α) signaling pathway, including decreased expression of p-AMPK, PGC-1α, nuclear factor-erythroid 2-related factor (NRF)-1, NRF-2, and the mitochondrial transcription factor A (TFAM), as well as reduced levels of mitochondrial DNA and damaged mitochondrial structure in the peritoneum [ 198 ]. In this model, treatment with metformin, an AMPK agonist, improved all these parameters and inhibited apoptosis of peritoneal MCs with the consequent improvement of peritoneal fibrosis [ 198 ].…”
Section: Potential Anti-inflammatory Treatments In the Preservation O...mentioning
confidence: 99%
“…In mice, PDF exposure downregulated the adenine monophosphate (AMP) activated protein kinase (AMPK)- peroxisome proliferator activated receptor-gamma coactivator-1 alpha (PGC-1α) signaling pathway, including decreased expression of p-AMPK, PGC-1α, nuclear factor-erythroid 2-related factor (NRF)-1, NRF-2, and the mitochondrial transcription factor A (TFAM), as well as reduced levels of mitochondrial DNA and damaged mitochondrial structure in the peritoneum [ 198 ]. In this model, treatment with metformin, an AMPK agonist, improved all these parameters and inhibited apoptosis of peritoneal MCs with the consequent improvement of peritoneal fibrosis [ 198 ]. Moreover, mitochonic acid-5 (MA-5), an indole-3-acetic acid derivative, has been shown to improve mitochondrial dysfunction and peritoneal damage in a model of peritoneal fibrosis induced by CG [ 199 ].…”
Section: Potential Anti-inflammatory Treatments In the Preservation O...mentioning
confidence: 99%
“…The levels of PGC-1α, NRF-1, NRF-2, and TFAM proteins were reduced in a mouse model of peritoneal fibrosis associated with peritoneal dialysis, indicating significant inhibition of mitochondrial biosynthesis. Metformin may partially act on the AMPK/PGC-1α pathway to increase mitochondrial DNA content, improve mitochondrial morphology, and enhance mitochondrial biosynthesis to reduce peritoneal dialysis related peritoneal fibrosis in mice ( 91 ).…”
Section: Mechanism Of Action Of Metforminmentioning
confidence: 99%